2021
DOI: 10.3389/fmicb.2021.742651
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Arbuscular Mycorrhizal Fungi Diversity and Community to 41-Year Rotation Fertilization in Brown Soil Region of Northeast China

Abstract: Arbuscular mycorrhizal fungi (AMF) play vital roles in the growth and development of plants, ecosystem sustainability, and stability in agroecosystem, such as transporting nutrients to host plants, improving soil physical structure, and enhancing the stress resistance of host plants. However, the effects of fertilization on AMF diversity and community in brown soil areas are still unclear. The purpose of this study is to explore changes in AMF diversity and community structures and finding out the factors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
(70 reference statements)
3
11
0
Order By: Relevance
“…The 12-year application of nitrogen fertilizer significantly reduced soil pH value and increased soil inorganic nitrogen ( Table 1 ). The decrease of soil pH might have been associated with a reduction or disappearance of some fungal taxa due to diminishment of the original habitat suitable for the growth of fungi ( Zhou et al, 2016 ), while the enrichment of nitrogen affected the adaptability of fungi, especially arbuscular mycorrhizal fungi, to the soil environment ( Zhang et al, 2021 ). In contrast to no correlation between the bacterial Shannon index and soil properties, the fungal Shannon index was positively correlated with a range of soil properties (i.e., SOC, TN, TP, TK, AP, AK), indicating that long-term fertilization had a greater impact on rhizosphere soil fungal diversity than bacterial diversity in aeolian sandy soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 12-year application of nitrogen fertilizer significantly reduced soil pH value and increased soil inorganic nitrogen ( Table 1 ). The decrease of soil pH might have been associated with a reduction or disappearance of some fungal taxa due to diminishment of the original habitat suitable for the growth of fungi ( Zhou et al, 2016 ), while the enrichment of nitrogen affected the adaptability of fungi, especially arbuscular mycorrhizal fungi, to the soil environment ( Zhang et al, 2021 ). In contrast to no correlation between the bacterial Shannon index and soil properties, the fungal Shannon index was positively correlated with a range of soil properties (i.e., SOC, TN, TP, TK, AP, AK), indicating that long-term fertilization had a greater impact on rhizosphere soil fungal diversity than bacterial diversity in aeolian sandy soil.…”
Section: Discussionmentioning
confidence: 99%
“… Bradley et al (2006) found N fertilization caused significant changes in the composition of soil fungal communities. Zhang et al (2021) showed that an appropriate amount of N could improve the efficiency of mycorrhizal symbiosis. In our study, soil fungal community was affected by soil carbon and nitrogen, which is consistent with the saprophytic status of most fungi ( Liu et al, 2015 ; Ding et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The field experiment was implemented with a soybean–maize–maize rotation, as described by Zhang et al. (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…The field experiment was implemented with a soybean-maizemaize rotation, as described by Zhang et al (2021). The six treatments included chemical fertilizer only (N, NP, and NPK) and manure combined with chemical fertilizer (MN, MNP, and MNPK).…”
Section: Field Experimentsmentioning
confidence: 99%
“…Second, the Archaeosporaceae could reflect the ability of AM fungi to promote P efficient utilization (Zhang et al, 2021). This also seems to imply that in AMF families or genera, it is not the higher abundance that is favorable for BBP.…”
Section: Arbuscular Mycorrhizal Fungi Community Structure Composition...mentioning
confidence: 99%